2011
DOI: 10.1002/adma.201101899
|View full text |Cite
|
Sign up to set email alerts
|

Choline‐Derivate‐Modified Nanoparticles for Brain‐Targeting Gene Delivery

Abstract: The choline transporter (ChT) is used to transporte choline‐derivate‐modified nanoparticles across the blood‐brain barrier. It is demonstrated that ChT is an ideal Trojan horse. The choline‐derivate‐modified nanoparticles exhibit higher permeability across the brain capillary endothelial cells (BCECs) monolayer in vitro and higher gene distribution and expression in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 19 publications
1
51
0
Order By: Relevance
“…However, the fl uorescence signals of the liver and kidney were apparently not captured in the whole body images (Figure 6 A-E). This might be attributed to the deep location of these organs, similar results of which have been reported by Li et al [ 49 ] …”
Section: Biological Applicationssupporting
confidence: 87%
“…However, the fl uorescence signals of the liver and kidney were apparently not captured in the whole body images (Figure 6 A-E). This might be attributed to the deep location of these organs, similar results of which have been reported by Li et al [ 49 ] …”
Section: Biological Applicationssupporting
confidence: 87%
“…2A, the modification of LNP significantly enhanced the permeability of NPs across the BBB at different time point. The P app of LNP-modified NPs which reached 92.43 Â 10 À6 cm/s, was larger than that of some other BBB crossing formulations such as lactoferrin-modified NPs (about 65 Â 10 À6 cm/s) [30] and the synthesized compound 10-conjugated NPs (about 40 Â 10 À6 cm/s) [31]. This indicated that the permeability promoting effect of LNP was more obvious than lactoferrin and compound 10.…”
Section: Transport Of Nps Across the Bbb Monolayermentioning
confidence: 85%
“…Several BBB-crossing strategies have been reported including receptor-based [30,33,34] and transporter-based [4,31] pathways. LNP has been reported to possess the potential for transporting biomolecules across the BBB [28].…”
Section: Transport Of Nps Across the Bbb Monolayermentioning
confidence: 99%
See 1 more Smart Citation
“…Several targeted drug delivery systems for brain diseases have recently been developed [5][6][7][8][9][10]. Targeted drug delivery systems can cross the BBB and promote accumulation of antitumor drugs in the brain.…”
Section: Introductionmentioning
confidence: 99%